Experimental Characterization of Dynamic Electrical Loading for Structural Battery Applications - Samanta, Suranjan; Deshpande, Sanjeev (My University, 2026)
Structural batteries, a recently developed technology, aims to combine energy storage and load-bearing capabilities within a single material system. Since early-stage structural battery prototypes are expected to be developed for small-scale applications before implementation in full-sized vehicles, there is a need for representative electrical loading conditions, operating requirements, and testing methodologies suitable for prototype development and evaluation. In this thesis, commercial 1:10 scale RC vehicle platforms were used as experimental platforms to investigate realistic electrical demands associated with small-scale mobility applications. Current and voltage measurements were collected during both sustained full-load operation and representative dynamic driving conditions in order to capture realistic mobility-related electrical behaviour. The measured data was analysed to characterize the sustained and transient current demand of both platforms, which were further used to develop representative electrical drive cycles. The resulting drive cycles establish representative operating requirements for future structural battery prototypes intended for these applications, while simultaneously providing a repeatable dynamic testing profile for prototype evaluation
Keywords: Structural Batteries; Prototype Evaluation; Drive Cycle; Small-Scale Mobility; RC Vehicles; Electrical Loading; Transient Response; Dynamic Testing; Electronic Load; Test Bench